The NSAIDs Indomethacin and Diflunisal as Scavengers of Photogenerated Reactive Oxygen Species1. (29th July 2013) - Purpora, Rebeca; Massad, Walter; Ferrari, Gabriela; Reynoso, Eugenia; Criado, Susana; Miskoski, Sandra; Pajares, Adriana; García, Norman A.
Abstract: Diflunisal (DFNS) and Indomethacin (IMTC) are two profusely employed NSAIDs that provide anti‐inflammatory and analgesic effects in humans. The scavenging of reactive oxygen species (ROS) by both NSAIDs was systematically studied in pH 7 aqueous solution. The ROS O2 ( 1 Δg ), O2 − and H2 O2, generated by visible light irradiation of Riboflavin (Rf) in the presence of DFNS and IMTC, are deactivated by the NSAIDs. The ROS scavenging action by both NSAIDs constitutes an interesting result and adds one more positive aspect to the beneficial actions attributed to these drugs. Nevertheless it should be taken into account that several NSAIDs, in particular IMTC, have been connected to the pathogenesis of gastric mucosal lesions, which in some cases includes ROS generating‐ability. DFNS quenches ROS in a dominant physical fashion. It constitutes an excellent protective‐antioxidant provided that is practically not destroyed/oxidized after the ROS scavenging action. IMTC, being also an efficient interceptor of ROS, belong to the so‐called group of sacrificial ‐ROS quenchers: It is easily degraded by the oxidative species in the scavenging action. Although this property is negative in the context of prolonged ROS elimination, exhibits a promissory aspect for the degradation of pharmaceutical contaminants, such as NSAIDs, in waste waters. Abstract : The scavenging of reactive oxygen species (ROS) by Diflunisal (DFNS) and Indomethacin (IMTC), two profusely employed anti‐inflammatory and analgesic NSAIDs, was systematically studied in pH 7 aqueous solution. The ROS O2 ( 1 Δg ), O2 − and H2 O2, generated by visible light irradiation of Riboflavin, are deactivated by the NSAIDs. DFNS quenches ROS in a dominant physical fashion. It constitutes an excellent protective‐antioxidant provided that is practically not destroyed/oxidized after the ROS scavenging action. IMTC, being also an efficient interceptor of ROS, belong to the so‐called group of sacrificial ‐ROS quenchers: It is easily degraded by the oxidative species in the scavenging action.